1989
DOI: 10.3109/02688698908992695
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tuberculous Osteomyelitis of Skull: Report of two cases

Abstract: Two cases of primary tuberculous osteomyelitis of skull confirmed by appropriate laboratory investigations are described here. Primary tuberculous osteomyelitis of skull is rare. Only two cases of chronic granulomatous osteomyelitis have been described so far in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Our patient was 3 years old. The condition is usually secondary to a primary focus elsewhere, mainly in the lungs 5 . Direct spread of infection from neighbouring structures such as the orbit, paranasal sinuses, face and nasal mucosa has also been implicated 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was 3 years old. The condition is usually secondary to a primary focus elsewhere, mainly in the lungs 5 . Direct spread of infection from neighbouring structures such as the orbit, paranasal sinuses, face and nasal mucosa has also been implicated 6 .…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9,12 The diagnosis was further supported by positive acid-fast bacilli staining in four cases, enzyme-linked immunosorbent assay seropositivity for Mycobacterium tuberculosis in three cases and an elevated ESR with positive Mantoux test in four case. In all cases, histopathological evaluation showed epithelioid, caseating granulomas.…”
Section: Discussionmentioning
confidence: 79%
“…9 However, two previous studies reported a higher mean age group. This is similar to the age group reported in a previous study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The overall incidence of skull tuberculosis is approximately 1/10,000 cases of tuberculosis (Davidson & Horowitz, 1970;Prinsloo & Kirsten, 1977). Tubercular osteomyelitis is caused by haematogenous or by lymphatic dissemination of bacilli from an active focus, usually in the lungs (Bhatia et al, 1980;Joseph et al, 1989). Many authors have stressed the importance of lymphatics in the spread of tuberculosis.…”
Section: Tubercular Osteomyelitismentioning
confidence: 99%